KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPOSISI DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 34 PADANG - Aieny, Melani Putri; Basri, Irfani (Universitas Negeri Padang, 2020)
ABSTRACT The purpose of this research was to describe things as follows. First, describes the reading skills in understanding of exposition textgrade VIIIJunior High School 34 Padang. Second, it describes the writing skills of expositon textgrade VIIIJunior High School 34 Padang. Third, explain the relationship between the reading skills in understanding of exposition text with writing skills of expositon textgrade VIIIJunior High School 34 Padang. This type of research correlation between the reading skills in understanding of exposition textwith writing skills of exposition text grade VIIIJunior High School 34 Padang is quantitative research with descriptive methods. Based on the reslt of the study, the following three things concluded. First, the reading skills in understanding of exposition text are in good qualification (77.56). Second, the writing skills of exposition on grade VIIIJunior High school 34 Padang are in good qalification (77.64). Third, there is a significant correlation between the reading skills in understanding of exposition text with the writing skills of exposition text grade VIII Junior High School 34 Padang at n-1 degress freedom and a sicnificant level of 95%. Kata Kunci: Korelasi, Keterampilan Membaca Pemahaman Teks Eksposisi, Keterampilan Menulis Teks Eksposisi